What are talent scouts actually identifying? Investigating the physical and technical skill match activity profiles of drafted and non-drafted U18 Australian footballers. Issue 5 (May 2016) - Woods, Carl T.; Joyce, Christopher; Robertson, Sam
Abstract: Objectives: To compare the physical and technical skill match activity profiles of drafted and non-drafted under 18 Australian football players. Design: Cross-sectional observational. Methods: In-game physical and skill variables were assessed for under 18 Australian football players participating within the 2013 and 2014 National under 18 Australian Football League Championships. Players originated from one State Academy ( n = 55). Ten games were analysed; resulting in 183 observations. Players were sub-divided into two groups; drafted/non-drafted. Microtechnology and a commercial statistical provider allowed the quantification of total distance (m), relative distance (m min −1 ), high speed running distance (>15 km h −1 ), high speed running expressed as a percentage of total distance (% total), total disposals, marks, contested possessions, uncontested possessions, inside 50s and rebound 50s ( n = 10). The effect size ( d ) of draft outcome on these criterion variables was calculated, with generalised estimating equations (GEE's) used to model which of these criterion variables was associated with draft outcome. Results: Contested possessions and inside 50s reflected large effect size differences between groups ( d = 1.01, d = 0.92, respectively). The GEE models revealed contested possessions as the strongest predictor of draft outcome, with inside 50s being the second. Comparatively, the remaining criterion variables were not predictive of draft outcome. Conclusions: Contested possessions and inside 50s are the most influential in-game variables associated with draft outcome for West Australian players competing within the National under 18 Australian Football League Championships. Technically skilled players who win contested possessions and deliver the ball inside 50 may be advantageously positioned for draft success.